UPAYA MENJAGA KEUTUHAN KELUARGA SAKINAH DIKALANGAN BURUH BANGUNAN PADA MASA PANDEMI COVID-19 (STUDI KASUS KELURAHAN WATES KOTA MOJOKERTO) - Masruhan Zamil; Ach Faisol; Shofiatul Jannah (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
The household conditions experienced by construction workers during the pandemic are quite worrying where the opinions obtained are very minimal, plus during the current pandemic, there are various kinds of basic needs that must be met. This study aims to answer the questions: 1). How is the implementation of the family of construction workers in Wates Village, Mojokerto City in maintaining the integrity of the Sakinah family during the covid19 pandemic. 2). How to fulfill the needs of construction workers' families in the perspective of Islamic law during the covid-19 pandemic in Wates Village, Mojokerto City. The research location is in Wates Village, Mojokerto City. The approach used is qualitative with the type of case study research. The results of this study indicate that the implementation of the family of construction workers in maintaining the integrity of the sakinah family during the covid19 pandemic is able to maintain family unity even in a pandemic period, namely by mutual openness between partners in terms of financial management, as well as establishing good communication with partners, both in terms of income and conditions that occur in the household. Fulfilling the needs of families of construction workers in the perspective of Islamic law is also divided into several parts, namely: primary, secondary and tertiary needs by the head of the family, as well as the fulfillment of needs by the head of the family while working as construction workers by seeking to borrow emergency funds needed during the pandemic. Kata kunci: Sakinah Family, Construction Workers, Covid-19 Pandemic.